The Effect of Supplementary Food in the Form of Moringa Leaf Dry Brownies on the Increasing Weight of Under-Fives with Underweight Status - Febriana Renitasari; Masini Masini; Ayuningtyas Ayuningtyas; Arum Lusiana (Poltekkes Kemenkes Semarang, 2023)
Background: In 2020, the percentage of underweight children under five in Indonesia is relatively high, which is 6.7% or a total of 779,139 children under five. Wonokerto Village is the village with the highest number of underweight children under five in Turi District. This shows that the problem of under-five malnutrition is still high both in Indonesia and in the regions, even though toddlers are a golden age where the growth process occurs very rapidly and cannot be repeated. Therefore, malnutrition in toddlers needs to be addressed immediately so that growth disorders do not occur. One alternative treatment is with dry brownies of Moringa leaves. Methods: This study used Pre Experimental designs, One Group Pretest and Posttest with a sample of 34 underweight toddlers who were intervened for 21 days and analyzed their weight gain using the Paired T-Test. Results: The results showed that there was an increase in underfive weight between before and after being given moringa leaf brownies with a p value of 0.000 < 0.05.. Conclusion: The conclusion is there is an effect of providing additional food in the form of dry brownies of Moringa leaves on increasing body weight in underfives with underweight status. All sections in the manuscript should be typed using Arial font. Authors should use this document as their article template. Articles must be written in A4 text size (210 x 297 mm) and the left margin format 25 mm, right margin 20 mm, top margin 30 mm, and bottom margin 20 mm. The manuscript must be written in Arial font with 11 pt font size (except article title, author name and abstract title), one space spacing, and in a two-column format (except for article title, author's name and abstract). The distance between columns is 5 mm (0.2 inches)